Increased Prevalence of Tricuspid Regurgitation in Patients with Prolactinomas Chronically Treated with Cabergoline - Colao, Annamaria; Galderisi, Maurizio; Di Sarno, Antonella; Pardo, Moira; Gaccione, Maria; D'Andrea, Marianna; Guerra, Ermelinda; Pivonello, Rosario; Lerro, Giuseppe; Lombardi, Gaetano (The journal of clinical endocrinology and metabolism, 2008)
Background: Cabergoline, a dopamine receptor-2 agonist used to treat prolactinomas, was associated with increased risk of cardiac valve disease in Parkinson’s disease. Objective: Our objective was to evaluate prevalence of cardiac valve regurgitation in cabergoline-treated patients with prolactinomas. Design and Setting: An observational, case-control study was conducted at a university hospital. Patients: Fifty treated patients (44 women and six men) and 50 sex- and age-matched control subjects participated; 20 de novo patients were also studied. Intervention: In the treated patients, the last cabergoline dose was 1.3 ± 1.3 mg/wk (<1 mg/wk in 44%, 1–3 mg/wk in 46%, and >3 mg/wk in 10%). Treatment duration was 12–60 months in 32% and more than 60 months in 68%. The cumulative (milligrams × months of treatment) dose of cabergoline ranged from 32–1938 mg (median 280 mg). Measurements: Valve regurgitation was assessed according to the recommendations of the American Society of Echocardiography. Results: In de novo patients, treated patients, and controls, the prevalence of mild regurgitation of mitral (35, 22, and 12%, P = 0.085), aortic (0, 4, and 2%, P = 0.59), tricuspid (55, 30, and 42%, P = 0.13) or pulmonic (20, 12, and 6%, P = 0.22) valves was similar. Conversely, the prevalence of moderate tricuspid regurgitation was higher in the treated patients (54%) than in de novo patients (0%) and controls (18%, P < 0.0001). Moderate tricuspid regurgitation was more frequent in patients receiving a cumulative dose above the median (72%) than in those receiving a lower dose (36%, P = 0.023). A higher systolic (P = 0.03) and diastolic blood pressure (P < 0.0001) was found in patients with than in those without moderate tricuspid regurgitation. Conclusion: Moderate tricuspid regurgitation is more frequent in patients taking cabergoline (at higher cumulative doses) than in de novo patients and control subjects, but the clinical significance of this finding has not been established. A complete echocardiographic assessment is indicated in patients treated long term with cabergoline, particularly in those requiring elevated doses.